PENGARUH PERPUTARAN MODAL KERJA TERHADAP PROFIT MARGIN - Dini Arifian; Furniawan Furniawan (Universitas La Tansa Mashiro, 2016)
This research is motivated problems that affect the profit margin on the sale of which is owned by the company, sooner or absence of working capital turnover that occurs in the company, and the sales rate changes up and down every year. The method used in this research is quantitative descriptive method, while the CV. Metassa Collection Desa Kadu Genep, Kecamatan Petir, Kabupaten Serang-Banten as the population, while the sample is financial statements for 2005-2014. Data analysis techniques in the study using simple linear regression analysis, correlation coefficient analysis, coefficient of determination, test data normality and hypothesis testing using t-test. Effect of working capital turnover of the profit margin of the test results obtained by the analysis of the correlation coefficient of 0.73, meaning that working capital turnover has a significant positive effect on profit margins, whereas if seen from the results obtained coefficient of determination of the effect of 53%. To increase profit margins CV. Metassa Collection able to add to working capital while lowering costs not to exceed the revenue, then sales of more scaled back, then profit margins will increase.